2018
DOI: 10.1029/2018jd028815
|View full text |Cite
|
Sign up to set email alerts
|

On the Upward Extension of the Polar Vortices Into the Mesosphere

Abstract: The polar vortices play a central role in vertically coupling the atmosphere from the ground to geospace by shaping the background wind field through which atmospheric waves propagate. This work extends the vertical range of previous polar vortex climatologies into the upper mesosphere. The mesospheric polar vortices are defined using the CO gradient method with Microwave Limb Sounder satellite data; the stratospheric polar vortices are defined using a stream function‐based algorithm with data from meteorologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 134 publications
(173 reference statements)
4
41
0
Order By: Relevance
“…At this altitude the model is in reasonable agreement with MLS in terms of both the GPH pattern (color fill) and polar vortex occurrence frequency. At this altitude level both the model and the observations show a broad circumpolar cyclone (in agreement with Harvey et al (), see their Figure 6) with an associated westerly jet (indicated by the white contour) that is stronger over the Pacific than over the Atlantic. Overall, the model displays a more zonally asymmetric distribution of vortex frequency than observed (the black contours are more elongated and spread out); this larger degree of zonal asymmetry in the model versus the observations is also reflected in DJF mean GPH at 75 km and is attributed to larger PWs in the model.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…At this altitude the model is in reasonable agreement with MLS in terms of both the GPH pattern (color fill) and polar vortex occurrence frequency. At this altitude level both the model and the observations show a broad circumpolar cyclone (in agreement with Harvey et al (), see their Figure 6) with an associated westerly jet (indicated by the white contour) that is stronger over the Pacific than over the Atlantic. Overall, the model displays a more zonally asymmetric distribution of vortex frequency than observed (the black contours are more elongated and spread out); this larger degree of zonal asymmetry in the model versus the observations is also reflected in DJF mean GPH at 75 km and is attributed to larger PWs in the model.…”
Section: Resultssupporting
confidence: 89%
“…Here we separate Arctic winters that exhibit a substantial mesospheric response to SSWs from years without such a response. We employ the conventions originally outlined by Tweedy et al () and later applied by Stray et al (), Limpasuvan et al (), and Harvey et al () to define SSW winters with an elevated stratopause (ES) event (see Manney et al (, ) and Tomikawa et al () for a detailed description of the observed meteorology during these events). Specifically, Arctic winters are considered to have an ES if they satisfy the following three criteria: (1) easterlies at the stratopause from 70°–90°N for five or more days, (2) 70°–90°N temperature is below 185 K, and (3) the polar stratopause “jumps” 10 km or more in altitude from its climatological altitude.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al, ; Yang et al, , ). The stratospheric polar vortex plays an important role in vertically coupling the atmosphere from the ground to geospace (Harvey et al, ). As suggested in recent studies (Garfinkel et al, , , G12 and G14 hereafter), the occurrence of stratospheric sudden warming (SSWs, Butler et al, ) could benefit from certain MJO phases by the modulated upward propagation of the wave number 1 (WN1) heat flux (e.g., Goss et al, ) in the troposphere and stratosphere.…”
Section: Introductionmentioning
confidence: 97%
“…The stratospheric ISO plays an important role in both tropospheric (Baldwin & Dunkerton, 1999;Polvani & Kushner, 2002;Sigmond et al, 2013) and middle atmospheric weather/climate variations (e.g., Manney et al, 2009;Leovy et al, 1985;K.-F. Li et al, 2013;Yang et al, 2017Yang et al, , 2018. The stratospheric polar vortex plays an important role in vertically coupling the atmosphere from the ground to geospace (Harvey et al, 2018). As suggested in recent studies (Garfinkel et al, 2012, 2014, G12 andG14 hereafter), the occurrence of stratospheric sudden warming (SSWs, Butler et al, 2015) could benefit from certain MJO phases by the modulated upward propagation of the wave number 1 (WN1) heat flux (e.g., Goss et al, 2016) in the troposphere and stratosphere.…”
Section: Introductionmentioning
confidence: 99%